Production and Quality Improvement of the Tropical Fruit Tamarind (Tamarindus indica Linn.) Wine - Pongkan, S.; Tilarux, P.; Charoensuk, K.; Ochaikul, D.; Suwanposri, A. (International Journal of Agricultural Technology, 2018)
Tamarind (Tamarindus indica Linn.) is one of the most popular tropical fruit with many benefits in Thailand. It have been used as a food ingredient for a long time and has many therapeutic properties. Therefore, The research finding was to produce and improve the quality of tamarind wine. The two varieties of Saccharomyces cerevisiae var. burgundy and montachae were chosen for tamarind wine fermentation. Both varieties produced similar percentages of alcohol by volume but for the sensory evaluation showed that montachae was better than burgundy with the 3.87 ± 0.10 points. The optimal conditions for production of tamarind wine was 10% inoculum concentration, 5% tamarind juice and 20 °Brix total soluble solid with the 0.67 percentage of alcohol by volume and 3.63 ± 0.10 points from sensory evaluation. Then the quality of tamarind wine was improved by mixing tamarind juice with pineapple juice and roselle juice. The result showed that, production of wine using only tamarind juice was obtained the maximum sensory evaluation result with 3.58 ± 0.24 points. In conclusion, tamarind can be used as substrate for production of wine. It will be meet an alternative way to add value to tamarind. Moreover, the produced tamarind wine had a good taste which the acceptance from the consumers without the quality improvement.